A randomized lifestyle intervention preventing gestational diabetes: effects on self-rated health from pregnancy to postpartum - Elina Engberg; Beata Stach-Lempinen; Kristiina Rönö; Hannu Kautiainen; Johan G. Eriksson; Saila B. Koivusalo (Journal of Psychosomatic Obstetrics and Gynecology, 2018)
Introduction: The purpose was to examine the effects of a randomized lifestyle intervention on self-rated health from pregnancy to postpartum in participants at high risk for gestational diabetes mellitus. Methods: We included 266 women with a history of gestational diabetes and/or prepregnancy BMI ≥30 kg/m2. The intervention group (n = 144) received individualized counseling on diet, physical activity, and weight management from trained nurses at six timepoints between the first trimester of pregnancy and 12 months postpartum, and met three times with a dietitian. The control group (n = 122) received standard antenatal care. We assessed self-rated health at the six timepoints by means of a single question with five response options ranging from good (1) to poor (5). Baseline-adjusted mean changes in self-rated health level were assessed with a mixed model for repeated measure methods. Results: The mean (SD) for self-rated health at baseline was 1.8 (0.8) in the intervention group and 2.1 (0.9) in the control group (p = 0.006). Self-rated health varied over time (time effect p < 0.001) and was the poorest in the third trimester. The sample indicated that self-rated health improved in the intervention group and deteriorated in the control group from the first trimester to 12 months postpartum, but the difference between the groups did not reach statistical significance (group effect p = 0.064). Discussion: The self-rated health level varied over time from the first trimester of pregnancy to 12 months postpartum in women at risk for gestational diabetes. Improving self-rated health among high-risk pregnant women through lifestyle intervention calls for further research.